2018
DOI: 10.4103/jcvjs.jcvjs_92_18
|View full text |Cite
|
Sign up to set email alerts
|

Autostabilization of neglected high-grade fracture–dislocation in the cervical spine

Abstract: Neglected cervical spine trauma is rare with very few case series reported in literature. There are no clear guidelines for its treatment. If operative treatment is sought, the role of skull traction, type of approach (anterior only, posterior only, or combined), sequence of surgery, type of instrumentation, etc., have to be considered. Hence, the treatment is challenging. Autostabilization has been described in the natural history of degenerative lumbar spondylolisthesis. As a result, many patients are treate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…17 Shah et al reported two cases with delayed presentation of cervical facet dislocation and observed autostabilization without any progression of deformity. 21 Bodman and Chin and Sulla and Mach made similar observations. 22,23 They concluded that once healed, these injuries are stable without surgical intervention.…”
Section: Discussionmentioning
confidence: 63%
“…17 Shah et al reported two cases with delayed presentation of cervical facet dislocation and observed autostabilization without any progression of deformity. 21 Bodman and Chin and Sulla and Mach made similar observations. 22,23 They concluded that once healed, these injuries are stable without surgical intervention.…”
Section: Discussionmentioning
confidence: 63%
“…Complications and events to anticipate include bleeding, prolonged hospital stay, need for ICU admission, wound complications, pseudoarthrosis, and fixation failure (Table 3). When surgical risks outweigh the benefits, conservative treatment is preferred [11,34].…”
Section: Treatment Goals and Expectationsmentioning
confidence: 99%
“…Thompson and Hohl [11] treated conservatively an asymptomatic alcoholic patient with bilateral cervical facet dislocation who presented years after the index trauma. Shah et al [34] reported 2 cases of neglected cervical facet dislocations that were managed conservatively. For all these cases, there was radiological fusion with moderate deformity, and without neurological deficit (Figure 5).…”
Section: Conservative Treatment Partial Reduction and In Situ Fusionmentioning
confidence: 99%